2022
DOI: 10.1152/ajpcell.00065.2022
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory networks coordinating mitochondrial quality control in skeletal muscle

Abstract: The adaptive plasticity of mitochondria within skeletal muscle is regulated by signals converging on a myriad of regulatory networks that operate during conditions of increased (i.e. exercise) and decreased (inactivity, disuse) energy requirements. Notably, some of the initial signals that induce adaptive responses are common to both conditions, differing in their magnitude and temporal pattern, to produce vastly opposing mitochondrial phenotypes. In response to exercise, signaling to PGC-1α and other regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…These proteins covered a variety of mitochondrial functions, as already described for high-functioning octogenarian master athletes [ 35 ], and supported the established knowledge that regular PA improves mitochondrial function [ 37 , 38 , 39 , 40 , 41 ], counteracting the decline in muscle strength and mass and in neuromuscular control [ 42 , 43 ]. In fact, the exercise-mediated coordinated expression of mitochondrial species activates mitochondrial biogenesis, which affects several functions within the organelle and triggers several signaling pathways [ 44 , 45 ] that are able to induce specific adaptations to the mechanical stimuli; among these, the increased oxidative capacity is a well-recognized hallmark of PA-mediated adaptation in the mitochondria [ 41 , 46 , 47 ]. Accordingly, by using different bioinformatic tools, in the overexpressed subset of this study, mitochondrial proteins involved in the oxidative metabolism were found, such as NDUFA7, NDUFA9, SUCLG1, UQCRH, ACAA2, ACADSB and ATP5J, confirming the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins covered a variety of mitochondrial functions, as already described for high-functioning octogenarian master athletes [ 35 ], and supported the established knowledge that regular PA improves mitochondrial function [ 37 , 38 , 39 , 40 , 41 ], counteracting the decline in muscle strength and mass and in neuromuscular control [ 42 , 43 ]. In fact, the exercise-mediated coordinated expression of mitochondrial species activates mitochondrial biogenesis, which affects several functions within the organelle and triggers several signaling pathways [ 44 , 45 ] that are able to induce specific adaptations to the mechanical stimuli; among these, the increased oxidative capacity is a well-recognized hallmark of PA-mediated adaptation in the mitochondria [ 41 , 46 , 47 ]. Accordingly, by using different bioinformatic tools, in the overexpressed subset of this study, mitochondrial proteins involved in the oxidative metabolism were found, such as NDUFA7, NDUFA9, SUCLG1, UQCRH, ACAA2, ACADSB and ATP5J, confirming the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a trend for a decrease in the expression levels of Nrf2 in the cocoa-supplemented animal model, which were significantly increased by exercise. Nrf2 is key in the coordination of redox mechanisms triggered by exercise [ 61 ], and is involved in the expression of antioxidant enzymes such as SOD [ 62 ]. Although it was not possible to measure the expression of Nrf2 in our athlete study, we did observe a decrease in systemic SOD activity, which supports the idea that cocoa intake modifies the expression of Nrf2 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a reduction in gene expression associated with cell cycle could impair growth and normal muscle maintenance (reviewed in [50]). Therefore, hypermethylation and suppression of gene expression within proteolysis, mitophagy and autophagy pathways, while perhaps counterintuitive as increases in these processes are observed in muscle wasting conditions such as cancer cachexia [51-53], this data is perhaps suggestive of a dysregulation in the genes involved in protein quality control processes in the SkM of cancer survivors. Where an inability to properly remove damaged cellular and mitochondrial proteins could contribute to impaired muscle function and quality [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hypermethylation and suppression of gene expression within proteolysis, mitophagy and autophagy pathways, while perhaps counterintuitive as increases in these processes are observed in muscle wasting conditions such as cancer cachexia [51-53], this data is perhaps suggestive of a dysregulation in the genes involved in protein quality control processes in the SkM of cancer survivors. Where an inability to properly remove damaged cellular and mitochondrial proteins could contribute to impaired muscle function and quality [53, 54]. For example, blocking autophagy is unable to spare muscle mass in mice with cancer cachexia, due to its role in protein quality control [55].…”
Section: Discussionmentioning
confidence: 99%